Right to Health in Nepal: Commitment versus Challenges - Khanal, Pratik (Health for All, 2015)
Nepal’s Interim Constitution 2007 addresses health as a fundamental right. The constitutional provision has set the platform for commencement of free health service program in Nepal. Recently, the New National Health Policy 2014 has been introduced which aims to devise different strategies to effectively implement Universal Health Coverage. Though concept of human right based approach has been integrated in different health development policies and plans, health system still faces different challenges in materializing health as a human right. This paper discusses on policy provisions as well as synchronization of Nepal’s efforts on fulfilling its commitment for right to health.Health for All Vol.,2 2014: 3-5